Habilidades linguísticas de crianças acometidas da Síndrome Congênita do Zika Vírus comparadas com crianças de desenvolvimento típico - Cunha, Divany Guedes Pereira da (2021)
Introduction: Microcephaly can be associated with different causes, including the vertical transmission by the Zika Virus (ZIKV), compromising neurological development and child. Objectives: To compare linguistic, cognitive, socialization, and independence skills in children with Zika Virus Congenital Syndrome. (CZVS) and typically developing children. Therefore, it was necessary to carry out a systematic review of the literature on the theme, characterize the child development of the studied population, describe the performance of the language skills of children with and without CZVS, describe the performance of cognitive skills of children with and without CZVS and describe the performance of socialization and independence skills of children with and without CZVS. Method: The study consisted of two stages, a systematic review and an observational one, case-control type, cross-sectional and quantitative study. The sample consisted of 20 children from the case group matched by sex and age (year and month) with 11 children without comorbidities and with typical development (control). The data collection was carried out in a single moment through an interview and the application of the DENVER II tests and observation of communicative behavior. Data were statistically analyzed. Results: Were found Statistical differences between the studied groups regarding linguistic, cognitive, and socialization/independence performance. The case group failed for all compatible skills with the children's chronological age, with low performance in the assessed skills, and equivalent age to six months, being approximately nine months in the language area and six months in the socialization area. The control group showed adequate performance in the assessed skills and an average age equivalent to five years; which confirms the proper development. Conclusion: Most children affected by ZIKV have skills related to screaming, turning to the sound, emitting guttural sounds, chirping, eye contact, smiling in response, and smiling spontaneously. The control group presented linguistic, cognitive, and socialization performance within the typical pattern. They use oral language as a communicative resource, with phonetic/phonological, syntactic, semantic, lexical, and pragmatic suitable constructions for their chronological age.